Effectiveness of endoscopic ultrasound-guided drainage for noncapsulated postoperative pancreatic collection. (October 2019) - Tamura, Takashi; Kitano, Masayuki; Kawai, Manabu; Tanioka, Kensuke; Itonaga, Masahiro; Kawaji, Yuki; Nuta, Junya; Hatamaru, Keiichi; Yamashita, Yasunobu; Kitahata, Yuji; Miyazawa, Motoki; Hirono, Seiko; et al.
Background: Postoperative pancreatic collection (POPC) is a frequent complication after pancreatectomy. Although percutaneous drainage (PD) has been the treatment of choice for POPC with encapsulation, endoscopic ultrasound-guided transmural drainage (EUS-TD) was recently reported effective for this condition. The main aim of this retrospective study was to compare EUS-TD and PD in terms of effectiveness and safety as the first procedure in patients with noncapsulated POPC. Methods: Consecutive patients who underwent pancreatectomy and developed noncapsulated POPC requiring EUS-TD or PD between April 2003 and May 2018 were enrolled. Noncapsulated POPC was defined as pancreatic collection appearing within 28 days postoperatively and lacking a thick encapsulating inflammatory wall on contrast-enhanced computed tomography. The effectiveness of drainage was compared between the two groups before and after propensity-score matching of patient characteristics. Outcomes of interest included re-intervention rate, number of re-interventions, immediate complication, remote complication, and time to clinical resolution after the procedure. Results: A sum of 81 patients were included: 14 underwent EUS-TD, and 67 underwent PD. There were significant differences between groups in POPC size and type of surgery. Propensity-score matching selected 13 patients who underwent EUS-TD and 28 who underwent PD. Re-intervention rate ( p = 0.045), and number of re-interventions ( p = 0.026) were significantly lower in the matched EUS-TD group than in the matched PD group. There were no significant between-group differences in immediate complication and remote complication. The time to clinical resolution after the procedure was significantly shorter in the matched EUS-TD than in the matched PD group (14 versus 26 days; p < 0.0001). Conclusion: EUS-TD is more effective than PD for drainage of noncapsulated POPC. EUS-TD should be considered as the first treatment of choice for noncapsulated POPC visible on EUS.